2007
DOI: 10.1016/j.specom.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Primitives-based evaluation and estimation of emotions in speech

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(172 citation statements)
references
References 26 publications
(30 reference statements)
9
148
0
1
Order By: Relevance
“…This result is consistent with some previous studies, which have suggested that emotional dimensions are more suitable to distinguish and describe the vocal expression of emotions than labels of discrete emotions CORNELIUS, 2003;LUGGER;YANG, 2007;PEREIRA, 2000;BARBOSA, 2009). Research on the automatic recognition of emotions from speech and speech synthesis can benefit from this finding, since the use of emotional dimensions may allow the reliable identification and synthesis of more subtle expressions of emotions and changes in speech expressiveness over time (GRIMM, et al, 2007;SCHRÖDER et al, 2001;BARBOSA, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with some previous studies, which have suggested that emotional dimensions are more suitable to distinguish and describe the vocal expression of emotions than labels of discrete emotions CORNELIUS, 2003;LUGGER;YANG, 2007;PEREIRA, 2000;BARBOSA, 2009). Research on the automatic recognition of emotions from speech and speech synthesis can benefit from this finding, since the use of emotional dimensions may allow the reliable identification and synthesis of more subtle expressions of emotions and changes in speech expressiveness over time (GRIMM, et al, 2007;SCHRÖDER et al, 2001;BARBOSA, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…fundamental frequency and intensity) and this may cause confusion when trying to describe these emotions by means of discrete labels (LUGGER;YANG, 2007;PEREIRA, 2000). Emotional dimensions may be useful for research on speech synthesis and automatic recognition of emotions from speech, since their continuous quality allows the modeling of weaker emotional expressions, as well as gradual changes in speech expressiveness over time (GRIMM et al, 2007;SCHRÖDER et al, 2001;BARBOSA, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Different researchers proposes values from k = 1 [23], [30] to k = 20 [14]. Usually the value of k is found by trial and error, different values are taken and the performance of these classifiers is compared [16], [17].…”
Section: A K-nnmentioning
confidence: 99%
“…Some studies (see for a review Murray & Arnott (1993) & Scherer (2003) have empirically investigated acoustic and prosodic characteristics such as pitch variables and speaking rate, which are taken into emotion recognition models and this approach has shown varying detection rates (Devillers et al, 2005). Table 1 shows some of the recognition accuracy of empirical evidence in the range of between 50% (Nakatsu et al, 2000) and 83.5% (Grimm et al, 2007). It should be noted that the accuracy may be dependent on the number of emotional states attempted in the studies.…”
Section: Related Literature On Emotion Recognitionmentioning
confidence: 99%
“…Recognition Rates Vocal 50% (Nakatsu et al, 2000),73% (Lee et al, 2006), 83.5% (Grimm et al, 2007) Facial 98% (Essa & Pentland, 1997), 86% (Anderson & McOwan, 2006), 78% (Ioannou et al, 2005) Body gestures 84-92% (Kapur et al, 2005),44-90% (Castellano et al, 2007) Of the above mentioned approaches, a physiological approach is promising in that inner bodily changes are reflected in autonomous nervous systems and thus, integrally related to human emotion (Picard et al, 2001;Lisetti et al, 2003;Zhihong et al, 2007). For example, there is empirical evidence that physiological activities in face, finger, and body (e.g., EMG, PPG, EEG) are related to emotions.…”
Section: Approachesmentioning
confidence: 99%